Fronteras No Mas - Staudt, Kathleen. author. aut Link
XII, 204 p.
Keywords: Fronteras No Mas examines the range of officials, non-government organizations, networks and remaining organizational vacuums that span the U.S. - Mexico border. Since NAFTA, more binational institutions and policies have emerged around the environment, business, and the labor force. This 'institutional shroud' facilitates the growth of civil society, yet cross-border organizing remains a challenging and complex version of local politics. Residents live and work within a region of vast economic inequalities and markedly different governments. The authors offer a civic blueprint on ways to enhance cooperation, given the almost certain future of increased interdependence in this North American space.